Design Of A Compact Patch Antenna Loading Periodic Jerusalem Crosses - Mi, Siya (2016)
A compact microstrip antenna loaded with periodic patterns etched in the ground plane is proposed. The etched patterns are Jerusalem crosses which look the same as one of the common electromagnetic band gap structures, uni-planar electromagnetic band gap. In this paper, the dielectric backed with etched ground plane is analysed in terms of metamaterial. The permittivity and permeability are derived from the simulated reflection and transmission coefficients. Then a patch is stacked on the metasubstrate, and the antenna is designed to operate at 2.4 GHz. The proposed antenna has a small dimension in comparison to two other published compact antennas. Compared to the conventional patch antenna, the proposed antenna achieves a 68.38% miniaturization of the patch, and a 2.84 times impedance bandwidth broadening. Furthermore, the operating frequency of the proposed antenna can be tuned over a large range of frequencies by physically adjusting the length of the surrounding slots or by voltage adjusting of the voltage controlled tunable inductive elements. The proposed antenna is fabricated and measured. The measurement results are found to agree well with the simulation ones.